Poly-Victimisation among Vietnamese High School Students: Prevalence and Demographic Correlates - Le, Minh T. H.; Holton, Sara; Nguyen, Huong Thanh; Wolfe, Rory; Fisher, Jane (PLOS ONE, 2015)
Background Exposure to multiple forms of violence, including abuse and crime is termed poly-victimisation. There has been increasing research interest in poly-victimisation among children and adolescents in high income countries. However, experiences among adolescents living in low- and lower-middle-income countries are yet to be examined. Aims To establish the prevalence of lifetime exposure to poly-victimisation and demographic characteristics of victims among high school students in Vietnam. Methods A cross-sectional survey with a self-report, anonymous questionnaire was conducted in ten high schools in Hanoi, Vietnam between October 2013 and January 2014. Poly-victimisation was assessed using the Juvenile Victimisation Questionnaire Revised 2 (JVQ R2). Results A total of 1,606/1,745 (92.0%) eligible students provided data and were included in the analyses. Lifetime exposure to at least one form of victimisation was reported by 94.3% (95%CI: 92.5-95.4%) of participants and lifetime exposure to more than 10 forms by 31.1% (95%CI: 27.8-33.5%). Poly-victimisation was associated with experiencing more adverse life events, having a chronic disease or disability, living with a step-parent, experiencing family life as unhappy, being disciplined at school, and living in a rural area. Poly-victimisation experiences differed among students from the three types of high schools in Vietnam. Conclusions These data reveal the prevalence and multi-factorial risks of exposure to poly-victimisation among adolescents in Vietnam. Prevalence rates of different forms of victimisation among Vietnamese students, including those previously un-investigated, were higher than those reported in other settings. Poly-victimisation was also common among them. There were certain subgroups who were more vulnerable to poly-victimisation. Further research to understand the broader aspects of adolescence in Vietnam, including poly-victimisation, is thus recommended. Special attention should be paid to specific subgroups in the prevention of violence against children and adolescents in this setting. Education to raise awareness about poly-victimisation among the community is needed.